Internal Audit Function and Good Corporate Governance as Determinants of Fraud Prevention in Islamic Banking: A Case Study of Bank Syariah Indonesia Banda Aceh - Evy Iskandar; Ayumiati; Muhammad Farhan; Akmal Riza; Ivon Jalil (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This study examines the influence of the internal audit function and Good Corporate Governance (GCG) on fraud prevention within an Islamic banking institution. Employing a quantitative research design with multiple linear regression analysis, data were collected from employees of Bank Syariah Indonesia Banda Aceh through structured questionnaires. The findings reveal that both internal audit and GCG have a positive and statistically significant effect on fraud prevention, both partially and simultaneously. Among the two variables, GCG demonstrates a more dominant contribution in strengthening fraud prevention mechanisms. These results indicate that effective governance structures, supported by risk-based internal audit practices, enhance the bank’s fraud risk management system. This study contributes to the growing body of literature on fraud prevention, particularly within the context of Islamic banking institutions.